2009
DOI: 10.1351/pac-con-08-09-15
|View full text |Cite
|
Sign up to set email alerts
|

Study of heat capacity enhancement in some nanostructured materials

Abstract: Heat capacity properties of some nanostructured oxides, metals, and zeolites were studied, mainly with the aid of low-temperature adiabatic calorimetry. Obvious enhancement in the heat capacity of nanostructured materials to different degrees was observed as compared with the corresponding coarse-grained materials. The contributions of enhanced heat capacity of nanostructured materials toward properties such as density, thermal expansion, sample purity, surface effect, and size effect are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“… Higher Cp of nanoparticles compared to their bulk counterpart. Reported by Tan et al ( 2009 ), the increased exposure of surface atoms is showed to increase the Cp value measured in various tested nanoparticles (Tan et al 2009 ). This mode is unlikely to play a major role in enhancement but might contribute to it.…”
Section: Resultsmentioning
confidence: 84%
“… Higher Cp of nanoparticles compared to their bulk counterpart. Reported by Tan et al ( 2009 ), the increased exposure of surface atoms is showed to increase the Cp value measured in various tested nanoparticles (Tan et al 2009 ). This mode is unlikely to play a major role in enhancement but might contribute to it.…”
Section: Resultsmentioning
confidence: 84%
“…The specific heat of smaller particles (Al 2 O 3 nanoparticle) size is more susceptible to temperature than that of larger particles (coarse-grained Al 2 O 3 ). The specific heat of small particles is higher for five main reasons: (1) smaller particle size means larger specific surface area (SSA), so the temperature affects the thermal expansion in the cluster of particle, (2) heat capacity is also larger because smaller particles are with larger porosity in the particle cluster at the same weight, (3) the smaller the particle size, the higher the number of particles; the interface layer between particles and particles or gas will also affect the specific heat, (4) the energy structure of nanostructured Al 2 O 3 is higher than that in a coarse-grained state [36], (5) the heat capacity of a grain boundary increases with an increment of the grain boundary's excess volume [37,38]: The excess specific heat depends on grain size [39]. For a particle size of 20 nm ( -Al 2 O 3 ) and a temperature of 25 -65 C, the specific heat ratio increases by 16.37% in the current experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…The density q was measured exploiting the Archimedes' principle. The specific heat c p was taken from the literature [45], neglecting possible contributions from doping and nanocrystallinity [46,47]. The synthesis-method itself should not have an impact on the specific heat [48].…”
Section: Characterizationmentioning
confidence: 99%